Diasporas: concepts, intersections, identities - Knott, Kim; McLoughlin, Seán (Zed Books, 2010)
Featuring essays by world-renowned scholars, Diasporas charts the various ways in which global population movements and associated social, political and cultural issues have been seen through the lens of diaspora. Wide-ranging and interdisciplinary, this collection considers critical concepts shaping the field, such as migration, ethnicity, post-colonialism and cosmopolitanism